Epidemiology of Tuberculosis in Multi-Host Wildlife Systems: Implications for Black (Diceros bicornis) and White (Ceratotherium simum) Rhinoceros - Dwyer, Rebecca A.; Witte, Carmel; Buss, Peter; Goosen, Wynand J.; Miller, Michele (Frontiers in Veterinary Science, 2020)
Cases of tuberculosis (TB) resulting from infection with Mycobacterium tuberculosis complex (MTBC) have been recorded in captive and semi-captive white (Ceratotherium simum) and black (Diceros bicornis) rhinoceros. More recently, cases have been documented in free-ranging populations of both species of rhinoceros in bovine tuberculosis (bTB) endemic areas of southern Africa. There is limited information on risk factors and transmission patterns for MTBC infections in African rhinoceros, however, extrapolation from literature on MTBC infections in other species and multi-host systems provides a foundation for understanding TB epidemiology in rhinoceros species. Current diagnostic tests include blood-based immunoassays but distinguishing between subclinical and active infections remains challenging due to the lack of diagnostic techniques. In other species models, demographic risk factors for MTBC infection include sex and age, where males and adults are generally at higher risk than females and younger individuals. Limited available historical information reflects similar age- and sex-associated patterns for TB in captive black and white rhinoceros, with more reports of MTBC-associated disease in black rhinoceros than in white rhinoceros. The degree of MTBC exposure in susceptible wildlife depends on their level of interaction, either directly with other infected individuals or indirectly through MTBC contaminated environments. Captive African rhinoceros have shown evidence of MTBC shedding, and although infection levels are low in free-ranging rhinoceros, there is a risk for intraspecies transmission. Free-ranging rhinoceros in bTB endemic areas may be exposed to MTBC from other infected host species, such as the African buffalo (Syncerus caffer), through shared environmental niches and resource co-utilization. This review describes current knowledge and information gaps regarding the epidemiology of TB in African rhinoceros.